Peran Faktor Internal dan Eksternal dalam Menyebabkan Kesulitan Belajar Siswa SMP Negeri 16 Surabaya - Sari, Fa'izah Dwi Kumala; Rofidah, Arini Nur; Kusuma, Risna Andara; Ramadhani, Dian (Lembaga Yasin AlSys, 2025)
The purpose of this study is to determine the factors of learning difficulties and the role of teachers in overcoming learning difficulties in students of SMP Negeri 16 Surabaya. This research method uses a qualitative method that allows us to determine the role of internal and external factors in causing learning difficulties in students at SMPN 16 Surabaya. Qualitative methods are methods of constructing reality and understanding its meaning, so this method pays close attention to processes, events and authenticity. This method is usually directly involved in interactions with the reality being studied. Based on the results of observations, there were several students who experienced learning difficulties and interviews with teachers showed that there were causes of students' learning difficulties, one of which was inadequate facilities and infrastructure and human resources who were less competent to teach. And according to students, the causes of learning difficulties were being lazy to read, and being bored to just listen to material without any practice. The conclusion of the study was that the factors causing learning difficulties were internal factors with indicators of fatigue and indicators of students' willingness to regain their enthusiasm. External factors of environmental aspects include social and non-social environments. And the role of teachers as facilitators, guides, and motivators is crucial in creating an effective learning atmosphere.